Distribution of two species of Nephropsis Wood-Mason, 1872 (Crustacea, Decapoda, Nephropidae) from northeastern Brazil - Alves-Júnior, Flavio De Almeida; Araújo, Marina De Sá Leitão Câmara De; Souza-Filho, Jesser F. (Zootaxa, 2016)
The genus Nephropsis Wood-Mason, 1872 has been reported from Brazil by Tavares (1998), Tavares & Young (2002), Silva et al. (2003), Dall´Occo et al. (2007) and Serejo et al. (2007), recording Nephropsis aculeata Smith, 1881, N. rosea Bate, 1888 and N. agassizii A. Milne-Edwards, 1880, the last of which occurs in both northeastern and southeastern of Brazil.